Analysis of elite male wrestlers' social comparison levels according to socio-demographic backgrounds - Halil Bısgın; Umit Ustun (Selcuk University, 2014)
Social comparison can be identified as a defensive tendency that people use as a means of self-evaluation. The aim of this study is to analyze social comparison levels of elite male wrestlers according to socio-demographic backgrounds such as age, participation year in wrestling; best achieved success and average monthly income. For this aim 79 elite men wrestlers volunteered. Turkish version of Alan amp; Gilbert's Social Comparison Scale was used as data gathering tool. Obtained data evaluated with SPSS 16 for Windows and in addition to descriptive statistical methods Frequency and Percentage,  One Way ANOVA was used to determine significant differences (Î±=0.05). As a conclusion no significant differences were found between sampling group's social comparison levels and their ages, sports year and their best success (p gt;0.05). Regarding that self-concept begins at early ages and the sport contributes to individuals, it is needed to make psychological counseling and guidance services in applying similar studies to different sample groups, widespread, easy to access and functional.